Dynamical systems and microphysics : geometry and mechanics : the proceedings of the 2nd International Seminar on Mathematical Theory of Dynamical Systems and Microphysics held at the International Center for Mechanical Sciences at Udine, Italy, from September 1 to 11, 1981 - Avez, A. (Andre); Blaquiere, Austin; Marzollo, Angelo (Academic Press, 1982)
Dynamical Systems and Microphysics.